Batak Toba Language Analysis (Phonoligical Point of View) - Affini, Laili Nur (ETERNAL, 2011)
Abstract Batak people speak a variety of closely related languages. The reason why the writers analyze Batak language is because the language is unique. The purpose is to find out the phonological similarities and differences between English and Batak Toba language also to conduct the premises of analyzing Batak Toba language to find out the existing and non-existing consonant and vowel sounds. The subject of the research is Netha AM Silalahi. The subject acts as the primary data source. Secondary data is gained from books and internet articles. Batak Toba language is unique. The writers found out that for words with two syllables, if the end of the first syllable is a consonant, and the beginning of the second syllable is a consonant, the sound of the last consonant in the first syllable will be dropped; first second syllable will get more pressure in its pronunciation. Key words: batak toba, pronunciation, phonological similarities, consonant and vowel sounds.